The effectiveness of dried cranberries ( Vaccinium macrocarpon) in men with lower urinary tract symptoms - Vidlář, Aleš; Vostálová, Jitka; Ulrichová, Jitka; Študent, Vladimír; Stejskal, David; Reichenbach, Richard; Vrbková, Jana; Růžička, Filip; Šimánek, Vilím (British Journal of Nutrition, 2010)
Lower urinary tract symptoms (LUTS) are a common condition in older men. The objective of the present study was to evaluate the efficacy and tolerability of cranberry (Vaccinium macrocarpon) powder in men at risk of prostate disease with LUTS, elevated prostate-specific antigen (PSA), negative prostate biopsy and clinically confirmed chronic non-bacterial prostatitis. Forty-two participants received either 1500 mg of the dried powdered cranberries per d for 6 months (cranberry group; n 21) or no cranberry treatment (control group; n 21). Physical examination, International Prostate Symptom Score, quality of life (QoL), five-item version of the International Index of Erectile Function (IIEF-5), basic clinical chemistry parameters, haematology, Se, testosterone, PSA (free and total), C-reactive protein (CRP), antioxidant status, transrectal ultrasound prostate volume, urinary flow rate, ultrasound-estimated post-void residual urine volume at baseline, and at 3 and 6 months, and urine ex vivo anti-adherence activity were determined in all subjects. In contrast to the control group, patients in the cranberry group had statistically significant improvement in International Prostate Symptom Score, QoL, urination parameters including voiding parameters (rate of urine flow, average flow, total volume and post-void residual urine volume), and lower total PSA level on day 180 of the study. There was no influence on blood testosterone or serum CRP levels. There was no statistically significant improvement in the control group. The results of the present trial are the first firm evidence that cranberries may ameliorate LUTS, independent of benign prostatic hyperplasia or C-reactive protein level.
Keywords: prášky, zásypy, pudry; prostata; Powders; Prostate; tobolky; lidé; Fruit; poruchy močení; Vaccinium macrocarpon; ovoce; hyperplazie prostaty; Male; Aged; lidé středního věku; Prostatic Hyperplasia; senioři; mužské pohlaví; Urination Disorders; Capsules; Middle Aged; Humans